The intergenerational transmission of education : new evidence from adoptions in the United States - Silles, Mary A. (Economica, 2017)
This article examines the influence of parental education on children’s grade-for-age using a large sample of adoptees drawn from the American Community Survey between 2008 and 2014. The results show that mother’s education is not an important determinant of the education of adopted children, despite statistically significant effects for own-birth children. The results for fathers are different. Among adopted white children, the effect of father’s education is shown to be a statistically significant determinant of grade retention. However, among black children, adoptive father’s education does not appear to have any discernible effect on children’s education. A range of sensitivity tests are undertaken to check the validity of these results. The differences in these patterns between white and black students suggest the presence of racial differences in the intergenerational transmission of education.
Keywords: Adoption; Education; Intergenerational mobility